The Legal Miracles in Zakat Collection and Study - Al Shareef, Badria Attieh Ayed (Journal of Humanities & Social Sciences, 2018)
The Qur’an is the eternal miracle in Islam. It is a miracle in its statement. It is miraculous in its legislation. This kind of legal miracle is one of the most important and miraculous aspects of the Quran. The Koran is considered the first legislation and therefore the objective of this study. Followed the method of extrapolation and analytical and tried to collect the legislative miracles in Zakat and then I study it. I have reached several results, including: Zakat in Islam in keeping with the age and development, including all that was introduced in this era of wealth by measuring what was in the era of prophecy On what is new in this era and its validity for all time and place, which shows a clear indication of the miraculous legislation of zakat